THE RELEVANCE OF THE UMAYYAH ISLAMIC EDUCATIONAL THINKING IN FORMING THE CURRICULUM HOLISTIC INDEPENDENCE - Ira Oktaria; Eva Dewi; Sahrul Mukhlis Lubis (RADJA PUBLIKA, 2024)
This research aims to determine the relevance of Umayyad Islamic educational thought in forming a holistic independent curriculum. The data collection technique in this research is through identifying discourse from books, papers or articles, magazines, journals, websites, blogs, or other information related to the title of the writing. The research method carried out here uses library research with discourse analysis. The research results show the relevance of Umayyad Islamic educational thought with the independent curriculum, including emphasizing Islamic religion-based teaching, emphasizing freedom of learning and critical thinking skills, emphasizing teaching moral values, developing creativity and innovation, and disseminating aspects of knowledge holistically. The conclusion of this research is that education today adapts to the more complex demands of the modern era. Educational thought in previous historical periods certainly had a big role in making a contribution to the world of education. Therefore, the current reforms must relate to the spiritual side so that a young generation is created that has skills, creativity, critical thinking and is religious.